Considerations about the Global Economic Restructuring and its impacts on territory - Ulisses da Cunha Baggio (GEOUSP: Espaço e Tempo, 2002)
The article intends to discuss the economic restructuring process in terms of globalization and its territorial impacts, and to evaluate the relations between the economical and political dimension of this socio-spatial dynamics.